Pengaruh Problem Based Learning terhadap Pemahaman Konsep Siswa pada Materi Isu-isu Lingkungan - Siska Dwi Anggraini; Dika Agustia Indrati (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to examine the effect of the Problem-Based Learning (PBL) model on students' conceptual understanding of environmental issues. This study used a quantitative approach with a pre-experimental one-group pretest-posttest design. The sample consisted of 30 ninth-grade D students at SMP Negeri 4 Tuban, selected using a purposive sampling technique. The instrument used was an essay test that measured students' conceptual understanding based on indicators including the ability to remember, understand, apply, analyze, evaluate, and generate new ideas. Data were analyzed using the N-gain test to assess changes in students' conceptual understanding. The results showed an increase in the average pre-test and post-test scores of 21.3, with an N-gain value of 0.55, which is considered moderate. This study has limitations because it was only conducted in a pilot class without involving a control class. Therefore, it is recommended that future research use a research design with a control group to increase external validity and broaden the generalizability of the research findings.